Penggunaan Kata Seru sebagai Foregrounding dalam Novel Durga Umayi Karya Y.B. Mangunwijaya: Kajian Stilistika - Alfian Rokhmansyah; NFN Purwanti; Pandu Pratama Putra (Madah: Jurnal Bahasa dan Sastra, 2018)
things to be conveyed and sometimes used to bring up a characteristic which can attracts the reader’s attention. The purpose of this research is to reveal the use of interjection as foregrounding in Durga Umayi novel by Y.B. Mangunwijaya. To achieve this goals, this research uses the concept of foregrounding contained in stylistics studies. This research is a library research with qualitative approach. Data collection using note taking and utilize card as research instrument. The results showed that the interjection used in Durga Umayi by Y.B. Mangunwijaya both singular and repetition, that is 44 interjections. The dominant interjection is ‘ya’ 150 words, ‘nah’ 45 words, ‘ah’ 45 words, and ‘kok’ 36 words.  In addition, there also some other interjection but not dominant. The repetition of interjection indicates that Durga Umayi isn’t a serious novel which will dictate the reader. Moreover, it will indicate a direct communication between the author and the reader.